Collaborating to prepare students for perioperative nursing - Lacey, Kimberly; Forte, Pamela; Tammaro, Marie (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Transforming clinical faculty preparation: A multistudent, multipatient simulation for nurse educator students - Kulacz, Regina; Lamberti, Amanda; Forte, Pamela; Lacey, Kimberly (Clinical Simulation in Nursing, 2026)
Keywords: Clinical Practice; Clinical faculty; Clinical judgment; Faculty development; Graduate students; Multipatient; Multistudent; Nurse education; Nurse educator; Nursing; Postgraduate; Role transition; Simulation; Student nurse; dept.nur